The Employment of EFL English Teachers’ Reflective Teaching: Types and Tools for Assessing Oneself - Wahyuni, Luh Gede Eka (LPPM Undiksha, 2023)
Reflecting on the teaching and learning process has been carried out as an important way of assessing oneself to improve teachers’ competence and professionalism. During blended learning in EFL classroom context, the results of the reflective teaching should be informative for teachers to know their teaching quality as well as to understand the students’ need and expectation in their learning. Thus, various reflective teaching strategies have been employed to enhance teachers’ reflective practice. This descriptive study is aimed to analyze the reflective teaching types and the strategies employed by the EFL English teachers in reflecting on their teaching. 17 secondary experienced English teachers were involved as the participants. Questionnaire and unstructured interview guide were administered to gather the data and the results were analyzed descriptively. The findings show that the English teachers tended to do reflection-in-action and reflection-on-action. They implemented various reflective teaching strategies such as students’ feedback, workshop or seminar, video recording, reflective journal writing, study-group, and class walk-through observation. Among those strategies, class walk-through observation done by the school supervisor was considered to be the least effective strategy. Portfolio, action-research, survey/questionnaire, and peer-observation were never conducted due to certain reasons. However, the discussion about the implementation of those reflective teaching strategies was limited in term of data collection in this study. Thus, several suggestions in relation to the limitation of the data findings are provided in this study.